Network meta-analysis and cost-effectiveness analysis comparing Cetuximab-β and Cetuximab for Chinese patients with RAS/BRAF wild-type metastatic colorectal cancer - Tong, Rongjun; Yang, Mengyu; Zhang, Wanjie; Zhou, Mengyuan; Wang, Linning; Lu, Yun; Chang, Feng (Frontiers in Pharmacology, 2025)
BackgroundThe escalating economic burden of metastatic colorectal cancer (mCRC) in China necessitates cost-effective first-line treatments. Cetuximab-β, a newer version of Cetuximab, is approved for first-line RAS/BRAF wild-type mCRC. This study evaluates the cost-effectiveness of Cetuximab-β with FOLFIRI for mCRC patients, comparing it to Cetuximab plus chemotherapy to guide clinical decision-making and policy development.MethodsWe conducted a network meta-analysis (NMA) of six randomized controlled trials to compare overall survival (OS), progression-free survival (PFS), and adverse events (AEs). Subsequently, a cost-effectiveness analysis (CEA) was performed using a 10-year partitioned survival model from the Chinese healthcare payer perspective. Costs were standardized to 2024 US dollars ($1 = ¥7.25). Both costs and outcomes were discounted annually at 5%. The model estimated life-years (LYs), quality-adjusted life-years (QALYs), total costs, and incremental cost-effectiveness ratios (ICER). Model uncertainty was evaluated via one-way sensitivity analysis, probabilistic sensitivity analysis, and scenario analyses.ResultsThe NMA showed comparable efficacy between Cetuximab-β and Cetuximab, with Cetuximab demonstrating an OS HR of 1.10 (95% CI 0.67–1.90) and a PFS HR of 0.94 (95% CI 0.49–1.80) compared with Cetuximab-β, along with a trend towards a more favorable safety profile for Cetuximab-β. CEA showed Cetuximab-β reduced costs by $12,005.54 ($34,996.43 vs. $47,001.97) and gained 0.10 QALYs (1.90 vs. 1.80 QALYs) versus Cetuximab, yielding a dominant ICER (-$120,743/QALY). Sensitivity and scenario analyses confirmed robustness.ConclusionCetuximab-β plus FOLFIRI represents a dominant, cost-saving strategy compared to Cetuximab plus chemotherapy for first-line treatment of RAS/BRAF wild-type mCRC in China.